An evaluation of a rapid conversion to teleSANE in response to COVID‐19. Issue 3 (28th July 2022) - Shaw, Jessica; Feeney, Hannah; Meunier‐Sham, Joan; Hazard, Karen; Plante, Pamela; Petricone, Randi
Abstract: Sexual Assault Nurse Examiners (SANEs) provide expert, comprehensive medical forensic care to patients who present for services following a sexual assault. Because SANEs are not consistently available, telehealth technology is being explored as a means to provide access to this expert care (i.e., teleSANE). During the COVID‐19 pandemic, teleSANE offered additional potential benefits by reducing the length of time spent and number of providers in patient exam rooms, the need for personal protective equipment that was in high demand and short supply, and provider anxiety related to providing in‐person care. In the summer of 2020, the Massachusetts SANE program rapidly and temporarily converted five hospitals from in‐person SANE care to teleSANE. An evaluation team interviewed 23 providers using a rapid research and evaluation methods approach to assess the temporary model and inform the future of SANE care. Evaluation findings reveal it is possible to rapidly and temporarily convert hospitals from in‐person to teleSANE care in a time of broad uncertainty, and that such a change requires intensive and thoughtful planning; a shared commitment to being supportive, flexible, and responsive; and specific experience and expertise. Considerations for communities exploring how best to ensure consistent, equitable access to SANEs are discussed. Highlights: Sexual Assault Nurse Examiners (SANEs) provide expert comprehensive medical forensic care to sexual assault patients. Telehealth technology is used to provide access to SANE expert care in some communities (teleSANE). TeleSANE offers unique potential benefits in the midst of a global pandemic, like COVID‐19. With intensive planning and expertise, in‐person SANE services can be rapidly converted to teleSANE. SANEs should be available to all patients seeking post‐assault care.